2016
DOI: 10.1007/s10439-016-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties and Microstructure of Heart Chambers: A Paired Comparison Study in an Ovine Model

Abstract: Mechanical properties of the cardiac tissue play an important role in normal heart function. The goal of this study was to determine the passive mechanical properties of all heart chambers through a paired comparison study in an ovine model. Ovine heart was used due its physiological and anatomical similarities to human heart. A total of 189 specimens from anterior and posterior portions of the left and right ventricles, atria, and appendages underwent biaxial mechanical testing. A Fung-type strain energy func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 28 publications
(32 reference statements)
2
29
0
Order By: Relevance
“…This is surprising given that the LVFW has a greater proportion of collagen. Our observation, of a greater ratio of collagen to myocyte fibres in the LVFW, is consistent with previous reports of higher collagen content preserving wall thickness during diastole and systole [51,[72][73][74] ( Table 2). Since a higher collagen content would typically be associated with greater stiffness in mature tissues, the less stiff behaviour observed here might be related to the collagen state in a 1-day neonatal heart.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is surprising given that the LVFW has a greater proportion of collagen. Our observation, of a greater ratio of collagen to myocyte fibres in the LVFW, is consistent with previous reports of higher collagen content preserving wall thickness during diastole and systole [51,[72][73][74] ( Table 2). Since a higher collagen content would typically be associated with greater stiffness in mature tissues, the less stiff behaviour observed here might be related to the collagen state in a 1-day neonatal heart.…”
Section: Discussionsupporting
confidence: 93%
“…This peak was then fitted with a Gaussian function, reporting the preferred fibre orientation [49,50]. A custom MATLAB code was also adopted to quantify the surface area ratio of collagen to myocyte fibres, using image thresholding based on RGB (red, green and blue) values [51].…”
Section: Fibre Orientation and Surface Area Calculations From Histolomentioning
confidence: 99%
“…While the uniaxial mechanical test offers a quicker and easier examination of the material mechanical property, the biaxial mechanical test better mimics the in vivo loading conditions and provides more comprehensive measurements of the anisotropic mechanical behavior [17,19,20,22,[39][40][41]. Both methods have been used in prior studies of LV and RV mechanical properties [17,20,[22][23][24][25][26][27][28][29][30][39][40][41][42][43][44][45][46] (please see Table 1 for a summary of these studies).…”
Section: Uniaxial and Biaxial Tensile Mechanical Testsmentioning
confidence: 99%
“…The characterization of the anisotropic behavior of ventricles is highly dependent on the definition of the biaxial coordinate system. To date, there are two main types of coordinate systems: the main fiber and cross-fiber coordinate system [17,30,44], and the outflow tract and cross-outflow tract coordinate system [20,29,40]. Using the former coordinate system, it is consistently observed that the tissue behaves stiffer in the fiber direction compared with the cross-fiber direction [22].…”
Section: Anisotropic Behavior Of Ventriclesmentioning
confidence: 99%
See 1 more Smart Citation